1971
DOI: 10.1002/bjs.1800580902
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar arteriovenous fistula for maintenance haemodialysis

Abstract: SUMMARYSixteen ulnar arteriovenous fistulae have been performed in 1 1 patients. Three immediate thromboses occurred in the same patient. Six late thromboses were observed: 2 after kidney transplantation and 4 after haemodialysis. Seven out of the 10 patients in whom the fistula was used were dialysed adequately from 5 weeks to 15 months. No adverse effect owing to the fistula was noted.THE creation of an arteriovenous fistula in the forearm allows haemodialysis to be carried out regularly and easily by simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Correlation between age and failure has not been described earlier. Ulnar artery-basilic vein fistulas have poorer patency rates as compared to the Brescia-Cimino fistula [8,9], with no significant difference between those made in the anatomical snuff box [10] and the elbow [11]. Our consolidated early failure rate (14.6%) is comparable with the overall failure rate in literature (9-12%) [12][13][14].…”
Section: Discussionsupporting
confidence: 63%
“…Correlation between age and failure has not been described earlier. Ulnar artery-basilic vein fistulas have poorer patency rates as compared to the Brescia-Cimino fistula [8,9], with no significant difference between those made in the anatomical snuff box [10] and the elbow [11]. Our consolidated early failure rate (14.6%) is comparable with the overall failure rate in literature (9-12%) [12][13][14].…”
Section: Discussionsupporting
confidence: 63%
“…Kinnaert et al (4) reported that in 15 of 18 patients, a UBF was created after ligation of the ipsilateral radial artery. They prevented distal ischemia by performing side‐to‐end anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Later, in 1968, McMillan and Evans (3) commented on a patient in whom a UBF had to be ligated after successful renal transplantation because of access‐related congestive heart failure. However, the first attempt to evaluate function and complications of UBF was done by Kinnaert et al (4) in 1971. Six years later, in 1977, the same author reported a high incidence of early failures and poor survival rates for UBF compared with other techniques (5).…”
mentioning
confidence: 99%
“…Therefore, this technique should not be discarded; it is a rather simple method of vascular access in patients where the classic site for arteriovenous fistulas cannot be used because of thrombosis or prior insertion of external shunts. Ulnar fistulas were also created successfully in patients in whom a classic radial-cephalic fistula had failed (Kinnaert et al, 1971).…”
Section: Discussionmentioning
confidence: 99%